Ingroup Empathy, Help, and Blame After Anti-LGBT+ Hate Crime - Paterson, Jenny (Journal of interpersonal violence, 2024)
Crimes motivated by hatred toward a person’s sexual orientation or gender identity typically cause greater physical and emotional harm than comparative crimes not motivated by hate. Compounding these impacts, hate crime victims receive less empathy, less support, and are blamed more for their victimization both by society in general and by criminal justice agencies. However, as hate crimes are the epitome of intergroup hostility, the crimes are also likely to engender an ingroup empathy bias in which fellow LGBT+ people provide greater empathy to hate crime victims, potentially motivating greater support and reducing victim blaming for these particularly marginalized victims. Across three studies, we examined LGBT+ participants’ empathic reactions to hate crime victims, along with their willingness to help victims and blame victims. In the Pilot Study (N = 131) and Study 1 (N = 600), we cross-sectionally showed that indirect experiences of hate crimes predicted a stronger LGBT+ identity which, in turn, was associated with greater empathy that predicted greater willingness to help victims and blame the victim less. In Study 2 (N = 657), we experimentally manipulated the motivation of a crime (hate vs. non-hate) and the group membership of the victim (ingroup-LGBT+ vs. outgroup-heterosexual) and found that crimes that had one or more group elements (i.e., involved an ingroup member and/or was motivated by hate) elicited greater empathy that, in turn, increased the willingness to help the victim and reduced victim blaming. Together, the findings provide cogent evidence that LGBT+ communities respond to anti-LGBT+ hate crimes with overwhelming empathy, and this ingroup empathy bias motivates helping behaviors and reduces victim blame, thereby buffering the marginalizing consequences of hate crimes. Policy implications include acknowledging and harnessing the importance of shared identities when practitioners and criminal justice agencies respond to anti-LGBT+ hate crimes.